Growth and Production of Hydroponic Melon (Cucumis Melo L.) Using DFT System with Gandasil B - Tappi, Oktavianus; Tandibayang, Robianto (CV. Publikasi Indonesia, 2025)
This study aims to identify and evaluate the economic value and production of hydroponic melon cultivation using Gandasil B, as well as the effect of its application on hydroponic melon (Cucumis melo L.), and to determine the most optimal dosage of Gandasil B. The research was conducted at the Greenhouse of the Faculty of Agriculture, UKI Toraja, Tallunglipu Subdistrict, North Toraja Regency, South Sulawesi, from March to June 2025. The method used was a Randomized Block Design (RBD) with four levels of Gandasil B treatment: (G0 = control), (G1 = 1.5 cc/liter of water), (G2 = 3 cc/liter of water), and (G3 = 4.5 cc/liter of water). The AB Mix concentration was applied as follows: 0–7 days after planting = 500 ppm, 8–14 days after planting = 750 ppm, 15–21 days after planting = 1000 ppm, 22–28 days after planting = 1250 ppm, 29–35 days after planting = 1500 ppm, and from 36 days until harvest = 2000 ppm. Observation variables included plant height, number of leaves, leaf diameter, number of branches, number of flowers, fruit diameter, fruit weight, and fruit weight per plot. Data were analyzed using analysis of variance (ANOVA) for RBD and followed by the Honestly Significant Difference (HSD) test at a 0.05 significance level